Perdas decorrentes do sistema de trilha na colheita mecanizada de arroz irrigado - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The harvest is the final step of the production process while the losses are be kept within acceptable standards. Lack of knowledge agronomic characteristics culture and impaired regulation of harvesters, combined with excessive speed shift, are considered the main factors responsible for grain losses in paddy crop. The present work aims quantify the losses in the harvest of rice two trail systems in different travel speeds. This experiment was conducted in March 2012, 2011/2012 season with the variety of rice IRGA 424, in the fields of production Granja 3 October Group Pitangueira in Itaqui-RS. The experimental design was a randomized 3 block with factorial, 2 x 5 to the heterogeneity, mainly on crop productivity, which may interfere with the results of losses. We evaluated the following parameters: track two mechanisms (rotor and pulls straw) and five speeds, 1 km h-¹, 1,5 km h-¹, 2 km h-¹, 2,5 km h-¹ e 3 km h-¹. The trail system demonstrated by axial rotor outperformed straw walker system, exhibited lower losses on sacks of rice per hectare, combined with an appropriate range of displacement speed between 1,5 to 2,5 km h-¹. In this system, gave a minimal loss possible with greater operational capacity, when compared to the system of straw walker in that rates above 2.0 km h-¹, reached high values of losses . Therefore, in times of dire need, when you want to harvest at higher speeds for the harvest targets are met, may be employed speeds between 2 km h-¹ and 3 km h-¹, at axial rotor system, It is not recommended, these higher speeds.
Keywords: Oryza sativa; Velocidade de deslocamento; Manutenção do maquinário; Displacement speed; Maintenance of machinery; CNPQ::CIENCIAS AGRARIAS